Analisis Penerapan Sistem Pengendalian Internal dalam Menunjang Efektifitas Sistem Pemberian Kredit pada KSP. Kopdit Tuke Jung Kantor Pusat Nelle (Jurnal Simki Economic, 2024)
This research aims to analyze the implementation of the internal control system in supporting the effectiveness of the credit granting system at KSP. Kopdit Tuke Jung Nelle Head Office. This research uses a qualitative descriptive approach to analyze the implementation of the internal control system in supporting the effectiveness of the credit granting system at KSP. Kopdit Tuke Jung Nelle Head Office. Primary data was obtained through interviews with KSP managers. Kopdit Tuke Jung Nelle Head Office uses a structured question guide. Secondary data was obtained from literature sources and literature studies. Data analysis was carried out by identifying the factors causing bad credit and the internal controls implemented at the Kopdit Tuke Jung cooperative, Nelle Head Office. Implementation of an internal control system to support the effectiveness of the credit granting system at KSP. Kopdit Tuke Jung Nelle head office has been implemented well. However, in the credit granting procedure there are components that have not been implemented optimally.